Characterization of Soil Profile Using Dispersion Curve Analysis - Hisbulloh Huda; Bagus Jaya Santosa (International Journal of Social Service and Research, 2022)
Research has been carried out on the seismic refraction exploration method by utilizing piles on the construction project of the Geomatics Campus II FTSP ITS Surabaya as a source of vibration. Rayleigh waves are one type of surface wave that is good for identifying layered structures near the earth's surface because 67% of the energy The total amount released by the seismic wave source is transmitted in the form of Rayleigh waves. In the layered medium, Rayleigh waves have dispersive properties, speed as a function of frequency. This property can be used to determine the structure of the earth's layers based on the shear wave velocity (Vs) with depth (h). The inversion process is carried out to match the measurement dispersion curve and the model. The result of the inversion process is the shear wave velocity (Vs) function of depth. This research is expected to identify and characterize the soil profile at the research site. On the track, there are three layers indicated as clay layers, in the first layer 0-6 meters with an average speed of 250 m/s, the second layer 6-19 meters with an average speed of 971 m/s, and the third layer 19-57 meters with an average speed of 1564 m/s